When standardized testing is not standardized. Issue 7 (22nd February 2022) - Nalliah, Romesh P.; Reddy, Michael
Abstract: Standardized testing has been utilized by K‐12 schools, undergraduate and graduate programs, as well as employers. Historically, it has been seen as an efficacious way to identify the best performing candidates to receive program entry or move forward in a hiring process. However, there is significant evidence mounting about the limitations of standardized testing and, yet, we persist with them because of their relative ease. The purpose of this perspective paper is to begin a conversation about the place of standardized tests in dental education and its relationship to institution goals related to diversity, equity, and inclusion.